Timing of high-intensity intermittent exercise affects ad libitum energy intake in overweight inactive men - Panissa, Valéria Leme Gonçalves; Julio, Ursula Ferreira; St-Pierre, David H.; Tavares da Silva Gomes, Alícia; Caldeira, Renan Santos [UNESP]; Lira, Fabio Santos [UNESP]; Takito, Monica Yuri; Franchini, Emerson (Elsevier, 2019)
The present study sought to clarify the impact of exercise intensity and timing on energy intake and appetite-related blood variables. Fourteen inactive overweight men were included in the study. Firstly, maximal aerobic power (MAP) was measured. Then, participants randomly performed 5 experimental sessions consisting of 30 min of steady-state exercise (SSE) at 50% of MAP, high-intensity intermittent exercise (HIIE) with 30s repetitions at MAP and 30s of passive recovery or no exercise (CTRL). Sessions were performed 1h (SSE1h and HIIE1h) or 2.5h (SSE2.5h and HIIE2.5h) after the consumption of a standardized breakfast. An ad libitum buffet was offered 3.5h after the completion of the breakfast. Absolute energy intake (EI) and relative energy intake (REI) (relative energy intake = energy intake - energy expenditure from exercise) were measured. Appetite (hunger, fullness and desire for specific foods) scores and circulating concentration of insulin and IL-6 were determined at 1h, 1.75h, 2.5h and 3.25h after breakfast while lactate was measured post-exercise. EI was greater after the CTRL session compared to HIIE2.5h (5045.9 ± 1873.5 kJ vs. 3716.1 ± 1688.7 kJ). REI was greater for the CTRL session (5045.9 ± 1873.5 kJ) than HIIE1h (3386.5 ± 1660.1 kJ), HIIE2.5h (2508.5 ± 1709.3 kJ) and SSE2.5h (3426.6 ± 1788.0 kJ). Higher hunger scores were observed following the CRTL session with respect to those of HIIE2.5h. Insulin and IL-6 concentrations were greater after HIIE1h and SSE1h with respect to those obtained after HIIE2.5h, SSE2.5h and CTRL. Lactate concentrations were higher in HIIE1h and HIIE2.5h compared to those of SSE1h and SSE2.5h. These results show that HIIE performed 2.5h after a breakfast reduced appetite (hunger scores) and EI through mechanism that need to be characterized. This approach can be applied to individuals aiming to create an energetic deficit.
Keywords: Appetite-regulating hormones; Cytokine; Energy intake; High-intensity intermittent exercise; Hunger